Mixed gonadal dysgenesis with normal karyotype : A rare case report - Anand Ajay; Gupta Narmada; Singh M; Mathur Sandeep; Nayyar Rishi (Wolters Kluwer Medknow Publications, 2010)
Mixed gonadal dysgenesis (MGD) presents as a unilateral testis, usually intraabdominal, a streak gonad on contralateral side, and persistent mullerian structures. 45X/45XY karyotype is most frequent in such cases with predominance of 45X cells in both peripheral lymphocytes and gonads. We present a rare case of a left undescended testis, normally descended right testis, with penoscrotal hypospadias, who had a normal karyotype and whose histopathological findings were endometrial tissue and fallopian tube in left testicular biopsy. Gonadal dysgenesis should always be kept a possibility in patient with undescended testis and proximal hypospadias. If karyotype reveals a 46XY gonadal dysgenesis, these patients need all the more careful follow-up to screen for gonadoblastoma in remaining normal testis. Subjecting the patients to prophylactic orchidectomy with hormone replacement can be an additional option in such patients.